UX analysis: A workout application focusing on elements of user experience and gamification - Carlsson, Andreas; Engelbrektsson, Felix; Larsson, Lisa; Nordström, Elin; Södergren, Mickaela (My University, 2018)
The purpose of the thesis was to examine what aspects make up a compelling user experience by developing a gym workout application for mobile phones. By combining research and collaborating with test users, an application for Android and iOS was developed and evaluated. By doing several iterations of the application it was possible to find out what contributes to a compelling user experience and implement this in a real product. Gamification increases the user experience and has the potential to motivate users. User experience is a subjective topic which makes it difficult to define. Aspects to consider are standardization, a logical ow and visual effects. The project outcome was an application released to the app stores as well as valuable insights into how user experience can make an impact on the usability of an application.
Keywords: Data- och informationsvetenskap; Computer and Information Science